2011
DOI: 10.1590/s1413-86702011000500009
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus detection and typing using a nested-PCR-RFLP assay

Abstract: BACKGROUND: It is clinically important to detect and type human papillomavirus (HPV) in a sensitive and specific manner. OBJECTIVES: Development of a nested-polymerase chain reaction-restriction fragment length polymorphism (nested-PCR-RFLP) assay to detect and type HPV based on the analysis of L1 gene. METHODS: Analysis of published DNA sequence of mucosal HPV types to select sequences of new primers. Design of an original nested-PCR assay using the new primers pair selected and classical MY09/11 primers. HPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(56 reference statements)
1
1
0
1
Order By: Relevance
“…The results of the present study identified a HPV infection prevalence of 34% in women attending a public health service in Cruz Alta. This result is, therefore, amongst the highest HPV prevalence values observed in Brazil to date and likely reflects the use of nested-PCR assays for data gathering, a method that has a higher analytical sensitivity compared with other HPV DNA detection strategies (Lipmann et al, 2010;Coser et al, 2011). Our HPV prevalence finding was also slightly higher than those previously found in populations within in the State of Rio Grande do Sul by PCR and hybrid capture analysis (Nonnenmacher et al, 2002;Rosa et al, 2008).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The results of the present study identified a HPV infection prevalence of 34% in women attending a public health service in Cruz Alta. This result is, therefore, amongst the highest HPV prevalence values observed in Brazil to date and likely reflects the use of nested-PCR assays for data gathering, a method that has a higher analytical sensitivity compared with other HPV DNA detection strategies (Lipmann et al, 2010;Coser et al, 2011). Our HPV prevalence finding was also slightly higher than those previously found in populations within in the State of Rio Grande do Sul by PCR and hybrid capture analysis (Nonnenmacher et al, 2002;Rosa et al, 2008).…”
Section: Discussionsupporting
confidence: 49%
“…For HPV DNA detection, genomic DNA was first extracted from samples using the silica method (Boom et al, 1990) and then amplified by nested polymerase chain reaction (nested-PCR) as previously described (Coser et al, 2011). Briefly, nested-PCR was performed with two DNA amplification rounds.…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…4,5 A infecção persistente por HR-HPV constitui o principal fator de risco para o desenvolvimento de neoplasia cervical 6 , onde cerca de 20-50% das mulheres infectadas são portadoras de múltiplos tipos de HR-HPV. 7 Considerando o importante papel da infecção pelo HPV no desenvolvimento do câncer do colo uterino, este estudo objetivou estimar a frequência da infecção por HPV e identificar os tipos virais mais prevalentes em amostras autocoletadas de mulheres jovens sexualmente ativas.…”
unclassified